Ta'līm Mahārāt al-Khaṭ al-'Arabī fī al-Katātīb al-Qur'ānīyah al-Ḥadīthah تعليم مهارات الخط العربي في الكتاتيب القرآنية الحديثة - غربا, أحمد (Universitas Negeri Malang, 2024)
Invention of writing has raised the status of human history above all other creatures, which clearly justifies its importance in communication, recording events, immortalizing monuments, and transmitting it from one generation to the next. We can understand from the above statement, the secret of Arabic Calligraphy, and what preserved it among different nations, and various fields of knowledge, and sufficient evidence of this is the association of the definition of illiteracy among all peoples with ignorance of reading and writing. Man has practiced writing since ancient times, as it has become an effective and efficient means of communication in its various forms, and thus it is considered one of the most important duties, especially in the field of learning and teaching languages to native and non-native speakers. The importance is also envisage by someone: “If it were not for the Calligraphies, covenants, conditions, records, deeds, and every agreement, security, contract, neighborhood, and alliance would be invalidated. On this basis, this paper aims to discuss the role of modern Quranic schools in teaching Arabic calligraphy to school-age pupils. The researcher used the descriptive method, and the study results concluded that kuttab schools have a positive effect in teaching pupils Moroccan Arabic calligraphy in a logical and scientific manner.